Comparison of commercially pure titanium surface hardness improvement by plasma nitrocarburizing and ion implantation - Darmawan, Agung Setyo (Trans Tech Publications, Switzerland, 2013)
Commercially pure (cp) titanium has a relative soft hardness property. In particular usage such as sliding, the improvement of the surface hardness will be required. In this study, surface hardness improvement of cp titanium by Plasma Nitrocarburizing and Ion Implantation are compared. Plasma Nitrocarburizing processes are conducted at different elevated temperatures with different duration processes, i.e. at 350 °C for 3, 4, and 5 hours, and at 450 °C for 2, 3, and 4 hours respectively, while Ion Implantation processes are conducted at room temperature and process durations are varied as 2.3 hours, 4.7 hours, and 9.3 hours. Nitrogen ions are used to implant the material. Hardness tests are then performed on each specimen by using Micro Vickers Hardness Tester. The surface hardness number (HV) for specimens of the Plasma Nitrocarburizing processes at temperature of 350 °C for process duration of 3 hours, 4 hours, and 5 hours are 74.16, 92.25 and 94.41, respectively while those at temperature of 450 °C for duration process of 2 hours, 3 hours, and 4 hours are 103.70, 121.31 and 126.17, respectively. The processes of Ion Implantation produce the surface hardness number (HV) of 88.97, 125.51, and 130.2, for duration processes of 2.3 hours, 4.7 hours, and 9.3 hours. The process of Ion Implantation produce higher surface hardness number than the Plasma Nitrocarburizing process at temperature 350 °C but the surface hardness number is lower when compared to the Plasma Nitrocarburizing at a temperature of 450 °C. For the duration processes 4 hours and more, the process of Ion Implantation produces the same surface hardness number with the Plasma Nitrocarburizing at temperature of 450 °C.